The honest politician's guide to prisons and probation - King, Roy D.; Willmott, Lucy (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Through a comprehensive analysis of legislative and organisational changes and interviews with all the key players, The Honest Politician's Guide to Prisons and Probation provides an authoritative account of the crisis which has gradually engulfed the prison and probation services since 1991. Setting out the nature and extent of the crisis, King and Willmott show how the Woolf agenda was overridden in a process of political churn, through explorations of the Conservative Government until 1997, New Labour, and the Coalition and Conservative Governments since 2010"--
OCLC-licensed vendor bibliographic record.
Keywords: Prisons -- History -- 20th century; Probation -- History -- 20th century; Prisons -- History -- 21st century; Probation -- History -- 21st century; Prisoners; Criminal justice, Administration of; POLITICAL SCIENCE / Government / General; SOCIAL SCIENCE / Criminology